Hand Preference and Creativity of Papua University Student - Vionita Putri; Elda Irma Jeanne Joice Kawulur; Febriza Dwiranti; Sabarita Sinuraya; Sita Ratnawati (Jurnal Penelitian Pendidikan IPA, 2022)
Human has a preference to use their hands for various manual activities. Left-handed preference is people who tend to use their left hand to perform various manual activities, while right-handed people tend to use right-handed. Any researches show that the left-handed preference for more creativity was influenced by the dominant use of the right brain and bigger corpus callosum. The research aims to determine the percentage of left-handed preference and their creativity in Universitas Papua, Manokwari Papua Barat. The method used in this research is the descriptive method. Data collection used a questionnaire to evaluate individual hand preference using Handedness Questionnaire and to determine individual creativity using Adjective Check List. The percentage of left-handed people in UNIPA were 9.3% or lower than right-handed and higher than ambidextrous. Our study supports the statement about selection in handedness in the traditional society which showed a higher percentage of left-hander as advantages related to using hand intensively.  The percentage of left-handed males and females was almost equal and strongly left-handed was higher in females. The percentage of creative people was higher in left-handed, especially in males